Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Eliminate the parameter. x = t^2 + 1, y = t^2 - 1.

Sagot :

Answer:

Eliminating the parameter, the equation is [tex]y = x - 2[/tex]

Step-by-step explanation:

We are given the following parametric equations:

[tex]x = t^2 + 1[/tex]

[tex]y = t^2 - 1[/tex]

We want to eliminate the parameter t. From the first equation:

[tex]x = t^2 + 1[/tex]

[tex]t^2 = x - 1[/tex]

Replacing in the second equation:

[tex]y = x - 1 - 1[/tex]

[tex]y = x - 2[/tex]

Eliminating the parameter, the equation is [tex]y = x - 2[/tex]

We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.